In Praise of Scripting: Real Programming Pragmatism. - Loui, Ronald P. (Computer (00189162), 2008)
The author offers opinions on the study and teaching of computer programming. He urges that programming scripting be taught as a means of introducing students to the topic before they are taught Java or other programming languages. Scripting is said to give programming students a basic flexibility in programming that will serve them in good stead if and when it becomes their profession.